Retrospective evaluation of the ST segment electrocardiographic features in 180 healthy dogs. (13th July 2022) - Romito, G.; Castagna, P.; Pelle, N. G.; Testa, F.; Sabetti, M. C.; Cipone, M.
Abstract : Objectives: Normal features of the ST segment are poorly characterised in dogs. This study aimed to describe ST segment characteristics in a population of healthy dogs. Materials and Methods: Medical records were reviewed to identify healthy dogs that underwent an electrocardiogram. Several ST segment qualitative parameters were evaluated: presence/absence of deviation, type of deviation (depression/elevation) and morphological patterns of depression (horizontal, downsloping, upsloping and sagging) and elevation (horizontal, concave and convex). Moreover, the amplitude of ST segment depression/elevation was measured. The potential effect of sex, bodyweight, age and somatotype on the presence/absence of ST segment deviation was evaluated through binary logistic regression. Results: One hundred and eighty dogs were enrolled. The deviation was evident in 43 of 180 dogs (23.9%), among which 36 showed depression and seven showed elevation. The median depression amplitude was 0.1 (range 0.05 to 0.3) mV. The mean elevation amplitude was 0.136 ±0.055 mV. Concerning depression morphology, the horizontal pattern was overrepresented, followed by the downsloping and upsloping ones. Concerning elevation morphology, all dogs showed a concave pattern. No meaningful effect of sex, bodyweight, age and somatotype on the presence/absence of ST segment deviation was documented. Clinical Significance: Normal features of canine ST segment were described and made available for clinical use.